Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/750814
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility for Lupus Nephritis by Low Copy Number of theFCGR3BGene Is Linked to Increased Levels of Pathogenic Autoantibodies

Abstract: Low copy number (CN) of the FCGR3B gene reduces FCGR3B membrane expression on neutrophils and results in clearance of a smaller amount of immune complex. We investigated FCGR3B CN in relation to the clinical phenotype in a Caucasian SLE cohort (n = 107). FCGR3B CN was determined by three different qPCR parameter estimations (Ct−, Cy0, and cpD1) and confirmed by the FCGR2C/FCGR2A paralog ratio test. Clinical and serological data were then analyzed for their association with FCGR3B CN. Low FCGR3B CN (<2) was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…The association between a low copy number of FCGR3B and LN is in accordance with studies in Afro-Caribbean and Caucasian populations (11)(12)(13)(14)(15) and is consistent with Chen et al's (8) and Niederer et al's (28) studies of Chinese populations. Furthermore, one previously published meta-analysis indicated that a low copy number of FCGR3B was a risk factor for LN (30), suggesting that there is a positive association between low copy number of FCGR3B and a risk of developing LN.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The association between a low copy number of FCGR3B and LN is in accordance with studies in Afro-Caribbean and Caucasian populations (11)(12)(13)(14)(15) and is consistent with Chen et al's (8) and Niederer et al's (28) studies of Chinese populations. Furthermore, one previously published meta-analysis indicated that a low copy number of FCGR3B was a risk factor for LN (30), suggesting that there is a positive association between low copy number of FCGR3B and a risk of developing LN.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies regarded FCGR3B CNV as a risk factor for a range of autoimmune diseases, including rheumatoid arthritis and SLE (11)(12)(13)(14)(15)27). A copy number <2 of FCGR3B has emerged as a susceptibility factor in Caucasian patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These association studies usually compare SLEassociated loci between those individuals with and without LN. Most of the susceptibility loci discovered by these strategies are related to immunity, such as complementmediated phagocytosis, antibody-mediated cytotoxicity, and T-cell function (Kim-Howard et al, 2009;Nossent et al, 2013;Qin et al, 2010;Zhou et al, 2010). While candidate gene association studies have provided important findings, this approach is based on assumptions about the pathogenesis of the disease, and is limited in its ability to identify new disease loci and pathways.…”
Section: Candidate-gene Association Studiesmentioning
confidence: 99%
“…46 The NA1 and NA2 alleles may also affect interactions with other cell surface receptors, such as the β2-integrin, CD11b/CD18 46 (ITGAM), whose genetic variants have also been linked to LN. 26,47,48 Low copy number of FCGR3A 49 and FCGR3B 50 have also been linked to LN.…”
Section: Extrarenal Etiologymentioning
confidence: 99%